Increased Central Nervous System Interleukin-8 in a Majority Postlaminectomy Syndrome Chronic Pain Population. Issue 5 (20th June 2017) - Giron, Sarah E; Bjurstrom, Martin F; Griffis, Charles A; Ferrante, F Michael; Wu, Irene I; Nicol, Andrea L; Grogan, Tristan R; Burkard, Joseph F; Irwin, Michael R; Breen, Elizabeth Crabb
Abstract: Background and Objectives: Multiple processes have been identified as potential contributors to chronic pain, with increasing evidence illustrating an association with aberrant levels of neuroimmune mediators. The primary objectives of the present study were to examine central nervous system cytokines, chemokines, and growth factors present in a chronic pain population and to explore patterns of the same mediator molecules over time. Secondary objectives explored the relationship of central and peripheral neuroimmune mediators while examining the levels of anxiety, depression, sleep quality, and perception of pain associated with the chronic pain patient experience. Methods: Cerebrospinal fluid (CSF) from a population of majority postlaminectomy syndrome patients (N = 8) was compared with control CSF samples (N = 30) to assess for significant differences in 10 cytokines, chemokines, and growth factors. The patient population was then followed over time, analyzing CSF, plasma, and psychobehavioral measures. Results: The present observational study is the first to demonstrate increased mean CSF levels of interleukin-8 (IL-8; P < 0.001) in a small population of majority postlaminectomy syndrome patients, as compared with a control population. Over time in pain patients, CSF levels of IL-8 increased significantly ( P < 0.001). Conclusions: These data indicate that IL-8 should be further investigated and psychobehavioral components considered in the overall chronic pain paradigm. Future studies examining the interactions between these factors and IL-8 may identify novel targets for treatment of persistent pain states.